2019
DOI: 10.1111/iej.13163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two shaping systems and two sonic irrigation devices in removing root canal filling material from distal roots of mandibular molars assessed by micro CT

Abstract: Aim To compare two preparation systems and two sonic irrigation devices during the removal of root filling material from oval distal canals of extracted mandibular molars. Methodology The distal canals in 40 extracted mandibular molars were shaped using the ProTaper Next system (Dentslpy Sirona, Ballaigues, Switzerland), filled with Gutta Percha X2 (Dentsply Sirona), along with AH Plus sealer (Dentsply De Trey, Konstanz, Germany) and randomly divided into two groups (n = 20) according to volume of initial fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Recent in vitro studies have shown that, compared with manual irrigation, the sonic irrigation device EDDY improves the dentin debris removal from artificial canal irregularities [14], the removal of calcium hydroxide from artificial grooves in the root canal of maxillary incisors [9], the removal of remnants of sealer and guttapercha [15] and the median dye penetration depths in dentinal tubules of apical root sections [16]. However, considering the pivotal etiopathogenetic role of endodontic biofilms in periapical disease, the reduction of the microbial load within root canal systems is arguably the most relevant surrogate marker in experimental irrigation studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies have shown that, compared with manual irrigation, the sonic irrigation device EDDY improves the dentin debris removal from artificial canal irregularities [14], the removal of calcium hydroxide from artificial grooves in the root canal of maxillary incisors [9], the removal of remnants of sealer and guttapercha [15] and the median dye penetration depths in dentinal tubules of apical root sections [16]. However, considering the pivotal etiopathogenetic role of endodontic biofilms in periapical disease, the reduction of the microbial load within root canal systems is arguably the most relevant surrogate marker in experimental irrigation studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Eddy instrument presented a significant reduction in the amount of remaining filling material, corroborating with the results found by Kaloustian et al (2019a). The effectiveness of this instrument is related, according to the manufacturers, to the formation of cavitation and acoustic streaming within the irrigant produced by the high frequency (6000 Hz) to which the polymer tip (Eddy) is used (Kaloustian et al 2019a).…”
Section: Discussionsupporting
confidence: 76%
“…Eddy (VDW, Munich, Germany) is a polymer tip that is activated by sonic vibrations by a conventional air scaler operating at a frequency of 6000 Hz . Studies have shown encouraging results where Eddy has been shown to be effective in biofilm and smear layer removal, and has improved the dissolution of organic tissue and removal of filling material during retreatment (Conde et al 2017, Urban et al 2017, Kaloustian et al 2019a, Swimberghe et al 2019.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Auch bei der Entfernung von Kalziumhydroxid, das als medikamentöse Einlage verwendet wurde, erwies sich der EDDY als der manuellen Spülung überlegen und der PUI vergleichbar [12]. Im Zuge von Revisionstherapien fördert der EDDY die Entfernung von Füllmaterial nach der mechanischen Entfernung mit Nickel-Titan-Instrumenten [22]. Im Modellversuch konnte ein Biofilm mit dem Endo-Activator ebenso wenig aufgelöst werden wie mit der manuellen Irrigation [11,23].…”
Section: Eddyunclassified